2010
DOI: 10.1016/j.actbio.2009.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release properties and final macroporosity of a pectin microspheres–calcium phosphate composite bone cement

Abstract: The use of calcium phosphate cements (CPC) is restricted by their lack of macroporosity and poor drug release properties. To overcome these two limitations, incorporating degradable polymer microparticles into CPC is an attractive option, as polymer microparticles could help to control drug release and induce macroporosity after degradation. Although few authors have yet tested synthetic polymers, the potentiality of polysaccharides' assuming this role has never been explored. Low-methoxy amidated pectins (LMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 37 publications
1
43
0
2
Order By: Relevance
“…For example, crystals of mannitol, CH 2 OH(CHOH) 4 CH 2 OH, were tested as an air-entraining agent; however, both loss of workability during the cement mixing and severe depreciation of mechanical properties were discovered simultaneously [296][297][298][299][300][301]. Other porogenic agents (e.g., oxygen peroxide [302] in the liquid phase and/or iced [303], sucrose granules, NaHCO 3 and Na 2 HPO 4 crystals of 125 -250 µm in size [304], poly(D,L-lactic-co-glycolic acid) microparticles with the average size of 66 ± 25 µm [305][306][307][308][309][310], pectin microspheres [311], calcium sulfate [46], calcite [219], NaCl crystals varying in size from 420 μm to 1 mm [312,313], gelatin microspheres [314,315], vesicants [316], cetyltrimethyl ammonium bromide [317], polytrimethylene carbonate [318], some immiscible liquids) have been also tested to create porosity. These additives could be applied on pre-set cements only, while the solubility degree of the particulates during the setting reaction influences both the content and dimensions of the macroporosity.…”
Section: Properties Improvingmentioning
confidence: 99%
“…For example, crystals of mannitol, CH 2 OH(CHOH) 4 CH 2 OH, were tested as an air-entraining agent; however, both loss of workability during the cement mixing and severe depreciation of mechanical properties were discovered simultaneously [296][297][298][299][300][301]. Other porogenic agents (e.g., oxygen peroxide [302] in the liquid phase and/or iced [303], sucrose granules, NaHCO 3 and Na 2 HPO 4 crystals of 125 -250 µm in size [304], poly(D,L-lactic-co-glycolic acid) microparticles with the average size of 66 ± 25 µm [305][306][307][308][309][310], pectin microspheres [311], calcium sulfate [46], calcite [219], NaCl crystals varying in size from 420 μm to 1 mm [312,313], gelatin microspheres [314,315], vesicants [316], cetyltrimethyl ammonium bromide [317], polytrimethylene carbonate [318], some immiscible liquids) have been also tested to create porosity. These additives could be applied on pre-set cements only, while the solubility degree of the particulates during the setting reaction influences both the content and dimensions of the macroporosity.…”
Section: Properties Improvingmentioning
confidence: 99%
“…Moreover, in several studies [18][19][20][21][22] the conditions used were not indicated. Hence, most studies in the literature disregard the fact that the release pattern may change depending on the time the cement was set for; only Canal et al compared the drug release patterns of cements set for different times (1 h vs 7 days), but this was done on apatitic cements only [10].…”
Section: Introductionmentioning
confidence: 99%
“…20,21 In most cases, the MS-containing composite structures were usually aimed to overcome the conventional limitations of tissue engineering scaffolds, especially poor drug delivery ability. Based on recent publications, it would be feasible to achieve a sustained release of a single biomolecule or sequential delivery of dual bioactive molecules for the tissue engineering application.…”
Section: In Vitro Lysozyme-release Kineticsmentioning
confidence: 99%